2004
DOI: 10.1603/0022-0493-97.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Red Imported Fire Ant on Cotton Aphid Population Density and Predation of Bollworm and Beet Armyworm Eggs

Abstract: The effects of the red imported fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae), on cotton aphid, Aphis gossypii Glover, populations and its predation of bollworm, Helicoverpa zea (Boddie), and beet armyworm, Spodoptera exigua (Hübner), (both Lepidoptera: Noctuidae) eggs were evaluated in cotton under field conditions during 2001 and 2002 in central and northern Texas. In central Texas, cotton aphid populations were approximately 5.5 times greater and predation of sentinel bollworm eggs 2 times gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Our results agree with prior work showing that fire ants make a substantial contribution to predation within crop canopies (Sterling et al , ; Diaz et al , ; Seagraves & McPherson, ; Butler et al , ; Tillman, ; Greenstone et al , ), and further demonstrate that they are also significant predators at the soil surface. In fact, between sites and across dates, fire ants made greater contributions to predation at the soil surface than within cotton foliage with the same prey type.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree with prior work showing that fire ants make a substantial contribution to predation within crop canopies (Sterling et al , ; Diaz et al , ; Seagraves & McPherson, ; Butler et al , ; Tillman, ; Greenstone et al , ), and further demonstrate that they are also significant predators at the soil surface. In fact, between sites and across dates, fire ants made greater contributions to predation at the soil surface than within cotton foliage with the same prey type.…”
Section: Discussionsupporting
confidence: 93%
“…The red imported fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae), is an opportunistic predator in agricultural systems, where it can directly increase predation by 20–30%, but can also decrease the abundance of many beneficial predators including lady beetles, lacewings, predatory hemipterans and spiders (Eubanks et al , ; Diaz et al , ). Red imported fire ants can contribute substantially to egg predation in crop foliage, and have been observed feeding on eggs of a variety of agriculturally important lepidopteran pests, including Helicoverpa zea (Boddie), Chrysodeixis includens (Walker) and Heliothis virescens (Fabr.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are documented studies of fire ant feeding on rednecked peanutworm Stegasta bosqueella (Chambers), sugarcane borer Diatraea saccharalis (Fabricius), beet armyworm Spodoptera exigua (Hübner), corn earworm Helicoverpa zea (Boddie), southern green stink bug Nezara viridula (Linnaeus), soybean looper Pseudoplusia includens (Walker), fall armyworm caterpillars Spodoptera frugiperda (J.E. Smith), boll weevil Anthonomus grandis (Boheman) and cotton aphid Aphis gossypii Glover (Sterling, ; Reagan, ; Nyffeler et al ., ; Fuller et al ., ; Vogt et al ., ; Diaz et al ., ). Some pests of medical importance fed upon by fire ants include lone star tick Amblyomma americanum (Linnaeus), horn fly Haematobia irritans (Linnaeus), and the mosquito species Psorophora columbiae (Dyar & Knab) and Aedes albopictus (Skuse) (Burnham et al ., ; Hu & Frank, ).…”
Section: Introductionmentioning
confidence: 97%
“…In Alabama, Georgia, and Texas, the predation potential of agronomic pests by S. invicta in agroecosystems has been reported especially on various stages of lepidopteran pests (Ruberson et al 1994;Diaz et al 2004;Styrsky & Eubanks 2010;Wickings & Ruberson 2016). Foraging individuals on plant canopies of cotton (Gossypium hirsutum L.; Malvaceae) and peanut (Arachis hypogaea L.; Fabaceae) have played a role as predators by removing the eggs of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) (Diaz et al 2004;Wickings & Ruberson 2016). A previous report by Diaz et al (2004) also indicated that early in the cotton season, S. invicta populations are attracted to the honeydew produced by aphid populations.…”
Section: Introductionmentioning
confidence: 99%